(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper we prove some new conditions for Cauchy sequences by using the diameter of orbit in partial metric spaces. A fixed point theorem for Meir-Keeler type contractions in this space is established.